Measuring student performance, student satisfaction and its impact on graduate employability - Abdullah, Zulhamri; Syed Alsagoff, Syed Agil; Ramlan, Mohd Fauzi; Sabran, Mohammad Shatar (Human Resource Management Academic Research Society, 2014)
The ever increasing of figures in the unemployment rate of graduates was mainly due to the fact that most of the graduates were released to the labor market well trained in their areas of specialization but without being fully equipped with skills that are required in the new economy world. The study seeks to examine the role of students development in the higher institutions. With the rise of business complexity and uncertainty around the world, currently employers have looked for talent and competencies of new workers who are capable of make a difference in their organization. Today’s business in public and private sectors is hampered by a shortage of skilled workers who should possess highly academic qualifications and excellent soft skills. We identify the status of student performance based on Chickering’s seven vectors, student satisfaction and their institutional image. A quantitative survey approach was employed in this study in the Northern University of Malaysia. 368 usable responses were sought in this study. The survey was self-administered in the classroom to increase the response rate from students. The findings from this research showed that most students are good at ‘Developing Mature Interpersonal Relationship’, followed by ‘Developing Integrity’. However, the average means score of ‘Developing Competence’ and ‘Managing Problem Solving and Critical Thinking’ is significantly affected the student performance. Most of students are above averagely satisfied with a university performance. Many perceived the institutional image are above averagely good. This study will contribute to both of theoretical and practical implications on the university’s student development.